2012
DOI: 10.1080/07055900.2012.742007
|View full text |Cite
|
Sign up to set email alerts
|

Current Observations of Internal Tides and Parametric Subharmonic Instability in Luzon Strait

Abstract: Acoustic Doppler Current Profiler (ADCP) measurements of the velocity structure in the thermocline in Luzon Strait are presented. The statistics for current, vertical variation of the inertia-gravity waveband, parametric subharmonic instability (PSI), and current shear are analyzed. It was found that 1) barotropic flow primarily consists of a nearly circular mixed tide. Diurnal tides are strongest and show smooth variance with a fortnightly spring-neap cycle, indicative of the astronomical tide-generating forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The overall quasi-periodic temporal variation of the current values for IT D 1 is shown, which is a signal for the spring-neap tide cycle. A similar phenomenon has been observed by other researchers (Liao et al, 2012;Xie et al, 2013). During most of the temporal series, the fi rst-mode IT D 1 currents dominated, and as a result, the overall D 1 component ( K 1 ) showed a fi rst-mode structure (Fig.3a).…”
Section: Temporal Variations Of the Multi-mode Internal Tidesupporting
confidence: 74%
“…The overall quasi-periodic temporal variation of the current values for IT D 1 is shown, which is a signal for the spring-neap tide cycle. A similar phenomenon has been observed by other researchers (Liao et al, 2012;Xie et al, 2013). During most of the temporal series, the fi rst-mode IT D 1 currents dominated, and as a result, the overall D 1 component ( K 1 ) showed a fi rst-mode structure (Fig.3a).…”
Section: Temporal Variations Of the Multi-mode Internal Tidesupporting
confidence: 74%
“…Following the recent observations [ van Haren et al ., ; van Haren, ; Xie et al . ; Liao et al, ], the internal wave band is not always a smooth broadband spectrum. The conventional view is that the bulk of internal wave energy is input at inertial and tidal frequencies, which cause nonlinear interactions (coupling) between near‐inertial and/or semidiurnal tidal motions to transfer energy to smaller scales, eventually ending in dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies [ Mihaly et al, ; van Haren et al ., ; van Haren, ; Alford et al, ; Alford, ; Xie et al . ; Liao et al, ; Chou et al ., ] provided solid evidence of nonlinear interactions between internal waves. Many numerical experiments [ Hibiya et al, 1998, ; Xing and Davies , ; MacKinnon and Winters, ; Furuichi et al, ; Gerkema et al, ] were carried out to investigate these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The bispectral analyses presented earlier (Figures a and 4b) showed that the [−O 1 , –K 1 , –M 2 ] triad has both elevated bispectral energy and significant bicoherence throughout a depth range > 200 m where the M 2 tide is energetic and beam‐like, evidence that has been interpreted as indicating nonlinear energy transfer in recent studies of PSI [e.g., Xie et al ., ; Liao et al ., ]. However, an experiment using the same bispectral techniques applied to a synthetic data set containing only deterministic tidal inputs and white Gaussian noise also resulted in elevated bispectral values and high bicoherence for the [−O 1 , −K 1 , −M 2 ] triad (Figures c and 4d), showing that these results do not always carry physical meaning [ Yao , ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerical and observational studies have suggested that direct and rapid energy transfer from the large-scale M 2 tide to small-scale oscillations at the M 2 subharmonic (M 2 /2, or M 1 ) frequency can occur for a range of latitudes equatorward of~29˚[e.g., Hibiya and Nagasawa, 2004;Gerkema et al, 2006]. Specifically, studies around the Kauai Channel [e.g., Carter and Gregg, 2006;Rainville and Pinkel, 2006;Sun and Pinkel, 2013] and the Luzon Strait [e.g., Xie et al, 2011;Liao et al, 2012] have inferred from observations that PSI is an identifiable mechanism of nonlinear energy transfer, even at tropical latitudes (~21˚N). The geographical extent of PSI acting on energetic internal tides is an important aspect of its relevance to diapycnal mixing in the global ocean.…”
Section: Introductionmentioning
confidence: 99%